Sunningdale : the search for peace in Northern Ireland - Dorr, Noel (Royal Irish Academy, 2017)
In this book a former Irish diplomat looks at British-Irish relations in the years leading up to Sunningdale, at the Conference itself and at some of the reasons why this initiative, born in hope, did not succeed. The book includes the author's own contemporaneous notes of the negotiations, which have not previously been published. At Sunningdale in December 1973, leaders of the two governments and of the unionist and nationalist communities reached a settlement aimed at bringing peace to Northern Ireland. The Irish government, for the first time, declared that there could be no change in the status of Northern Ireland until a majority of the people of the area desired it; the British government declared that if the majority indicated a wish to become part of a united Ireland they would support that wish; and all the participants agreed on new political institutions to promote cooperation and reconciliation within Northern Ireland and between both parts of the island. Sunningdale did not succeed in its immediate objective of achieving peace, and there were still difficulties at times in Anglo-Irish relations. But the precedent set for close cooperation between the two governments in relation to Northern Ireland, and many of the concepts developed at that time, were to prove of great importance to subsequent efforts to resolve the Northern Ireland conflict, up to and including the peace achieved under the Good Friday/Belfast Agreement of 1998.--